Synthesis of some heterocycle containing urea derivatives and their anti-viral activity - Verma M.; Singh K.N.; Clercq E.D. (My University, 2025)
Some new isoindol heterocyclic ureas (6a-6i) have been synthesized using N-aminophthalimide (2) and ethyl N-monosubstituted/ethyl N,N-disubstituted carbamate (5a-5i). All the newly synthesized final compounds have been evaluated for their anti-viral activities against a variety of viruses. The compound (6f) with the methoxy substituent showed reasonably better activity as compared to the standard drugs against all the viruses (cf. Tables 1, 2 and 3). Further, all the products (6a-6i) were found to be active against Vesicular stomatitis virus, Coxsackie virus B4 and Respiratory syncytical virus (cf. Table 2) and the compounds (6h) and (6i) displayed better antiviral activity in comparison to Brivudin and (S)-DHPA (cf. Table 3). © 2006 The Japan Institute of Heterocyclic Chemistry.